Numerical Investigation of the Free Surface in a Model Mold. Issue 2 (2nd April 2015) - Asad, Amjad; Kratzsch, Christoph; Schwarze, Rüdiger
Abstract : The transient‐free surface behavior in a model mold is evaluated numerically by performing the unsteady Reynolds‐averaged Navier‐Stokes (RANS) simulation and the two‐phase approach volume of fluid (VOF). Simulation is conducted in this study by means of the open source computational fluid dynamics library OpenFOAM ® . The calculations indicate the effect of nozzle depth and jet velocity at the nozzle port on the free surface profile. Recent experimental results are used to validate the free surface contour gained from the numerical simulations. A good overall agreement is found between experiment and simulation. The typical single‐roll and double‐roll are observed in the mold depending on the nozzle depth and the inlet velocity. Abstract : In the present paper, Numerical simulation is conducted by means of OpenFOAM ® with aim to capture the transient behavior of the free surface. The numerical prediction is validated by using recent experimental results, where a good overall agreement is shown. The flow pattern, time‐averaged free surface profile and spatio‐temporal plots of the meniscus elevation are indicated.